Gambaran Faktor Risiko Keluhan Muskuloskeletal pada Pengrajin Tenun Motif Sumba di Desa Rindi, Kabupaten Sumba Timur - Hendrik Mandaha; Agus Setyobudi; Noorce Ch. Berek (Media Kesehatan Masyarakat, 2022)
Musculoskeletal disorders are complaints related to the muscle tissue system caused by certain types of work activities and body postures. Weavers may likely experience the disorders due to the weaving-related activities such as unnatural posture, length of work, and individual characteristic factors. Musculoskeletal complaints can be the initial cause of disability. The purpose of this study was to describe the risk factors for musculoskeletal complaints in weavers in Rindi Village, East Sumba Regency. This type of research is descriptive with an observational research design. A total of 60 female weavers were selected as the research sample. The study showed that the weavers who often experienced serious complaints of MSDs were in the age group ≥ 30 years, with work period more than 4 years, and work duration reached ≥ 8 hours per day. Weavers should adjust the duration of weaving and reduce repetitive movements. Weavers are recommended to take a rest for 30-60 minutes and to work in an ergonomic posture without putting excessive loads on certain parts of the body.